Sustainable Industrial Approaches: Utilizing Organic Acid for Purity Enhancement in Green Silica Production - Aulia Cahyani; Purwanto Purwanto (Engineering Proceedings, 2025)
Green silica synthesis from rice husk ash represents a viable solution for promoting environmental sustainability in industrial applications. Conventional silica produced in industrial processes is often crystalline and carcinogenic, posing significant health risks to humans and environmental hazards. In this study, the production of high-purity green silica was achieved through the application of acetic acid (CH3COOH) and tartaric acid (C4H6O6) as chelating agents to effectively remove impurities. Acid leaching was performed with varying temperatures (25 °C and 75 °C) and durations (1 and 2 h). The results revealed green silica achieved SiO2 purity of 92.21%, with the complete removal of MgO, P2O5, TiO2, and CaO. The amorphous phase content is notably at 61.26%. Morphological analysis and surface area characterization confirmed an average adsorption pore size of 28.87 nm and a uniform pore size distribution of green silica in the 35–50 nm range. The surface properties and pore characteristics of the synthesized green silica meet the specifications for mesoporous silica, making it suitable for industrial purposes. This method highlights a potential alternative pathway and promotes the adoption of safe and environmentally benign chemicals, contributing to both material innovation and environmental sustainability.